The role of the Notch signalling pathway in the pathogenesis of ulcerative colitis: from the perspective of intestinal mucosal barrier - Ning, Hang; Liu, Jiemin; Tan, Jiaqian; Yi, Mengni; Lin, Xiaoyuan (Frontiers in Medicine, 2024)
Ulcerative colitis is a common digestive disorder worldwide, with increasing incidence in recent years. It is an urgent problem to be solved, as it seriously affects and threatens the health and life of the global population. Studies have shown that dysfunction of the intestinal mucosal barrier is a critical pathogenic factor and molecular basis of ulcerative colitis, and some scholars have described it as a “barrier organ disease.” While the Notch signalling pathway affects a series of cellular processes, including proliferation, differentiation, development, migration, and apoptosis. Therefore, it can regulate intestinal stem cells, CD4+ T cells, innate lymphoid cells, macrophages, and intestinal microbiota and intervene in the chemical, physical, immune, and biological mucosal barriers in cases of ulcerative colitis. The Notch signalling pathway associated with the pathogenesis of ulcerative colitis has distinct characteristics, with good regulatory effects on the mucosal barrier. However, research on ulcerative colitis has mainly focused on immune regulation, anti-inflammatory activity, and antioxidant stress; therefore, the study of the Notch signalling pathway suggests the possibility of understanding the pathogenesis of ulcerative colitis from another perspective. In this article we explore the role and mechanism of the Notch signalling pathway in the pathogenesis of ulcerative colitis from the perspective of the intestinal mucosal barrier to provide new targets and theoretical support for further research on the pathogenesis and clinical treatment of ulcerative colitis.